Translational Research in Medical Informatics or from Theory to Practice - Lehmann, C. U.; Altuwaijri, M. M.; Li, Y. C.; Ball, M. J.; Haux, R. (Methods of Information in Medicine, 2008)
Objective: To bridge the divide between health informatics ‘bench research’ and the application of informatics in clinical and health care settings.Method: Identifying weak points in translational activities, i.e. in the process from health informatics research outcomes to IT system design and information management in clinical practice.Results and Conclusions: The creation of a new peer-reviewed journal, designed to cultivate broad readership across health care, is suggested in order to communicate on informatics topics of translational interest and on the application of informatics principals. Such an applied informatics journal may appeal to practicing physicians, healthcare administrators and CIOs as well as medical informaticians. In a globalizing world with eHealth initiatives spanning across borders, such a journal should be an international effort. Close ties to the International Medical Informatics Association (IMIA) and to the journal Methods of Information in Medicine are suggested.
Keywords: Translational research; health informatics; medical informatics; IMIA